Amorphous silica mobilization by inter‐rill erosion: insights from rainfall experiments. Issue 9 (4th February 2015) - Clymans, Wim; Struyf, Eric; Van den Putte, An; Langhans, Christoph; Wang, Zhengang; Govers, Gerard
Abstract Amorphous silica (ASi) carried in suspension by rivers is an important component in the global Si budget. Water erosion processes in cultivated catchments are likely to drive ASi delivery to the river system. However, no studies have investigated the controls on ASi mobilization by erosional processes in croplands. Rainfall experiments were performed on split fields (i.e. a part conventionally ploughed and a part under reduced tillage) to simulate ASi mobilization by inter‐rill erosion in croplands, and identify its dependency on soil, field and rainfall characteristics. The ASi content of the soil and the inter‐rill erosion rate were determined as the major controls on ASi mobilization. Variables such as tillage technique and crop type did not have a consistent direct or indirect effect. Inter‐rill erosion is clearly selective with respect to ASi, indicating association of ASi with the fine soil fraction and with soil organic carbon. Our experiments demonstrate that erosion increases due to human perturbation will increase the delivery of reactive Si to aquatic systems. We estimate that globally, c. 7% of all reactive Si that enters aquatic systems is derived from erosion of agricultural soils. Copyright © 2015 John Wiley & Sons, Ltd.